2014
DOI: 10.1007/s10734-014-9795-0
|View full text |Cite
|
Sign up to set email alerts
|

Identity issues: expatriate professors teaching and researching in Qatar

Abstract: Today, academics are more transient, working outside their home countries, than at any other time in the history of academics especially in the Arab World were there is great demand for faculty members educated in Western' culture and academia. However, many of these professors face considerable social, professional and academic challenges in teaching and research. This paper presents the voices of twenty expatriate professors (EPs) as they describe their experiences and conflicts they face teaching in GCC uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Staff employed at international branch campuses often perceive injustice in their places of work. Injustices include the lack of legal rights, lack of job security, and inequalities in pay and benefits among employees of different nationalities (Romanowski and Nasser 2015). Altbach (2001) argues that academic freedom is at the very core of the mission of universities, and that it is essential to both effective teaching and research.…”
Section: Host Country Stakeholdersmentioning
confidence: 99%
“…Staff employed at international branch campuses often perceive injustice in their places of work. Injustices include the lack of legal rights, lack of job security, and inequalities in pay and benefits among employees of different nationalities (Romanowski and Nasser 2015). Altbach (2001) argues that academic freedom is at the very core of the mission of universities, and that it is essential to both effective teaching and research.…”
Section: Host Country Stakeholdersmentioning
confidence: 99%
“…A few studies examine foreign academics working in the UK (Gimenez and Morgan 2017). Overall, these studies on USA and UK examine issues such as cultural adaptation, work productivity (Mamiseishvili and Rosser 2010;Franzoni et al 2014), job satisfaction and coping mechanisms (Collins 2008;Romanowski and Nasser 2015), and faculty retention (Lawrence et al 2014). Well-established higher education systems naturally attract scholars from around the world without the need to actively recruit internationally.…”
Section: The Context Of Higher Educationmentioning
confidence: 99%
“…A number of studies have found that expatriate academics do not always experience positive relationships with their local colleagues. Romanowski and Nasser (2014) and Schoepp (2011) indicated that their participants felt excluded from collegial networks, particularly when the majority of their colleagues were host nationals. Although the expatriates' good social relations with their students may not necessarily lessen the feelings of exclusion and isolation from their colleagues, we predict that such good social relations to the students can work as a compensating job resource to enhance job satisfaction (cf.…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…The level of mobility among academics has increased dramatically in recent years (Romanowski and Nasser, 2014;Selmer et al, 2017). An important reason for academics to travel between countries for work is the global competition for talent (Isakovic and Whitman, 2013;Silvanto and Ryan, 2014).…”
Section: Introductionmentioning
confidence: 99%